(3SQGL GdYGQajf hYeOI GdePcQjf hefHg GdZGadjfs - (3ajQhR GdfGUMjs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO bGd GdTjN GdEeGe ajQhR GdfGUMi QVi Gddg Yfg CNHQJ eeG HdZfG QShd Gddg Udi Gddg Ydjg hSde Cda MOjK UMjM ai eGFI aQZ hSejJg SQGLO GdYGQajf s
(3BNQgG (B:s
(3heG ETJQi YHO HOjfGQ Ch HfUa KhHkG aMeO Gddg JYGdi Ydjg MJi jdHSg de jHdZ QcHJg MJi jZaQ Gddg dg hGdSGHY eG Qhi s
(3HgG fXGe GdJYbjHIs
(3cJHJ YfGhjjf GdCHhGH heOGNd GdCMGOjK HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
Keywords: (3GdMOjK h GdeUWdMs